A tale of two genera: Exotic Eucalyptus and Acacia species in China. 2. Plantation resource development. (1st June 2020) - Arnold, R.J.; Xie, Y.J.; Luo, J.Z.; Wang, H.R.; Midgley, S.J.
In China a substantial plantation industry involving 5.4 M ha of exotic eucalypts and up to 50 000 ha of exotic acacias, has been built on a foundation of collaborative R&D sponsored by both China and Australia over the past 40 years. Germplasm derived from some of the early collaboration still provides the majority of trees deployed in current eucalypt plantations in China. But, whilst the past 2 decades has been the best of times for plantation eucalypts in China, the past decade has simultaneously been the worst of times for plantation acacias. Improved plantation productivities achieved through R&D programs coupled with innovations in processing markedly increased the profitability of young eucalypt plantations; this provided strong market pull for expansion of these plantations. For exotic acacias though, plantation areas in China have declined over the past decade. Factors that have contributed to the contrasting fates of these species in China, along with their future outlooks, are reviewed in this report.